STRATEGI PENGEMBANGAN KEMITRAAN AGROINDUSTRI NILAM DI KABUPATEN KONAWE SELATAN MENGGUNAKAN METODE ANALISIS SWOT DAN AHP - Dzulkarnain; Imam Santoso; Siti Asmaul Mustaniroh (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Patchouli oil is one of the export commodities of essential oil which has high economic value. This shows the need to develop patchouli oil cultivation and processing at the farm level, especially in South Konawe Regency. The purpose of this study was to obtain an agro-industry strategy in terms of partnerships both in the production and marketing aspects. The stages of this research began from the field study by interviewing patchouli oil agro-industry actors in South Konawe. The analytical method used was a combination of SWOT (Strengths, Weaknesses, Opportunities, Threats) and Analytical Hierarchy Process (AHP) techniques to get strategic priorities. The results of this study found that the patchouli agro-industry partnership system applied today consists of two patterns including the plasma core pattern for the production aspect and the general trade pattern for the marketing aspect. Furthermore, the alternative strategy that has the highest priority was to increase wider market access by establishing partnerships with a score of 0.369, the second priority was to conduct training in human resource development in collaboration with related agencies with a score of 0.250. The third priority was to strengthen capital by utilizing business networks and the internet to overcome the price game with a score of 0.206, and the last priority was to expand partnerships (parthnership) of patchouli farmers and entrepreneurs in increasing production. Keywords: patchouli oil, partnership, development strategy, SWOT, AHP